2020
DOI: 10.1002/tie.22185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of predeparture and postarrival cross‐cultural trainings on expatriates adjustment: A study of Chinese expatriates in Nigeria

Abstract: The increase in economic globalization has created a need for multinational corporations to use expatriates to manage their foreign subsidiaries. Expatriate employees face many challenges that they can meet successfully only if they are well prepared through sound cross‐cultural training. In this exploratory study, we investigated the effects of cross‐cultural training on Chinese expatriates in Nigeria. We mainly focused on the relationship between predeparture and postarrival cross‐cultural training. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 75 publications
2
10
0
Order By: Relevance
“…Moreover, the moderating test results indicated that the training phase was not a significant moderator for the CCT–adjustment relationship. In fact, while CCT exhibited a slightly larger relationship with adjustment in an in-country stage rather than a pre-departure stage, consistent with prior findings (Selmer, 1998; Wang and Tran, 2012; Wurtz, 2014; Okpara et al. , 2021), the two relationships did not have significant differences.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, the moderating test results indicated that the training phase was not a significant moderator for the CCT–adjustment relationship. In fact, while CCT exhibited a slightly larger relationship with adjustment in an in-country stage rather than a pre-departure stage, consistent with prior findings (Selmer, 1998; Wang and Tran, 2012; Wurtz, 2014; Okpara et al. , 2021), the two relationships did not have significant differences.…”
Section: Discussionsupporting
confidence: 88%
“…departure stage, consistent with prior findings (Selmer, 1998;Wang and Tran, 2012;Wurtz, 2014;Okpara et al, 2021), the two relationships did not have significant differences. We urge more preliminary studies on post-arrival CCT and on the continuity of the training phase to optimize the trainees' adjustment.…”
Section: Impact Of Cross-cultural Trainingsupporting
confidence: 87%
See 1 more Smart Citation
“…Flexpatriates are frequent flyers who perform a wide range of duties by crossing cultural and national boundaries at a short notice and over short time spans while maintaining their family lives in their home country (Mayerhofer, Hartmann, & Herbert, 2004 ). Flexpatriation is catching momentum because of lower costs associated with it as there is no movement of the family, lower training costs, less time for preparation, and adjustment, and relatively simpler compensation packages (Collings & Isichei, 2018 ; Farndale et al, 2014 ; Okpara, Kabongo, & Lau, 2020 ). Secondly, with the rise in dual‐career partnerships, employees are not comfortable relocating to foreign location because of spouse's career (Harvey, Ronald Buckley, Novicevic, & Wiese, 1999 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the most critical foreign employee's cultural intelligence affected this process by improving cross-cultural living and working conditions. As a result, it is essential to provide training and other modalities that would enhance employees' CQ because, as the study of Okpara et al (2020) pointed out, training had significant and positive influences on expatriates' adjustment. An employer with high levels of CQ can help leaders recognize their leaders' transformational behaviors and enhance employees' job performance (Nam & Park, 2019) which should be very important for the cross-cultural adjustment of foreign employees.…”
mentioning
confidence: 99%